An empowerment-based, healthy dietary behavioral intervention to ameliorate functional constipation - Wang, Xuesong; Zhong, Xiaohui; Liu, Dongsong; Cao, Hong; Chen, Jing; Wang, Qinyue; Xia, Yanping; Zhang, Feng (Frontiers in Nutrition, 2023)
Objective: To explore the boost effect on ameliorating functional constipation in elderly patients through empowerment-based, healthy dietary behavioral intervention. Design: In this randomised parallel group study, elderly patients with functional constipation were recruited and assigned to the experimental and control groups at a ratio of 1:1. The control group received routine intervention. The experimental group received 3-month empowerment-based intervention. The results were evaluated based on the Healthy Lifestyle and Personal Control Questionnaire (HLPCQ) and Cleveland Clinic Constipation Score (CCS). GraphPad Prism (Version 9) software was used for the statistical analysis. Setting: As the world's population ages, functional constipation in the elderly has attracted widespread attention. The practical behavioral intervention to ameliorate constipation are worth exploring. Participants: Sixty elderly patients with functional constipation. Results: The study results showed no significant difference in the baseline data between the two groups (P > 0.05). After the intervention, the scores of HLPCQ (77.90 ± 14.57 vs. 61.11 ± 13.64) and CCS (7.48 ± 3.73 vs. 9.70 ± 3.07) in the experimental group were significantly higher than those in the control group (P < 0.05). Conclusion: The results showed that empowerment-based intervention can effectively strengthen the healthy dietary behaviour of elderly patients. Through patient empowerment, the subjective initiative and willingness to communicate were boosted in the experimental group. Their symptoms of functional constipation improved considerably better than in the control group.